A metropolitan scale analysis of the impacts of future electricity mix alternatives on the water-energy nexus. (15th December 2019) - Mounir, Adil; Mascaro, Giuseppe; White, Dave D.
Highlights: Future water-energy interactions are modeled in the Phoenix Metropolitan region. Fast transition to renewable energy will save water and reduce CO2 emissions. Intense droughts will slightly reduce energy used by water infrastructure. Costs of renewable and business as usual scenarios are comparable. Abstract: Current population and climate trends are increasing the need to adopt holistic approaches for managing water and energy systems, especially in water-limited regions like the Southwestern U.S. In this study, we quantify the implications of future energy mix alternatives on the water-energy nexus in the Phoenix, Arizona metropolitan region using the Long-range Energy Alternatives Planning (LEAP) platform. We first show that LEAP is able to simulate historical observations of energy generation and consumption from 2001 to 2018. We then simulate future electricity generation through 2060 under the same demand projections and different energy mix solutions. Results of our simulations are as follows. (i) Water heating accounts for 71% of the total water-related uses and its energy needs are projected to double in 2060, due to population growth; the energy required to treat and move water is instead expected to decrease by 9%, mainly because of declining agricultural water demands. (ii) Energy mix solutions that transition faster to renewable sources are more sustainable than a business as usual scenario that relies more on fossil fuels, because renewable technologies require less water for electricity generation (−35%) and reduce CO2 emissions (−57%). (iii) The aggressive transition to renewable energy is projected to have higher structural costs than the business as usual scenario, but comparable total expenses because of the lower operational cost of renewable technologies. This work complements and expands previous regional studies focused on the Southwestern U.S. and supports current efforts of local stakeholder engagement initiated by the authors.